The Influence of Diet on Overweight Status in Adolescent Students of SMK Muhammadiyah 3 Purwokerto - Adit Ferdinan; Ragil Setiyabudi (LPPM Universitas Harapan Bangsa, 2025)
According to SIRKESNAS 2022, in Indonesia, 13.5% of individuals aged 18 years experience excess weight, with 28.7% being overweight with a BMI of 25 and around 15.4% being overweight with a BMI of 27. Being overweight is a condition where body weight exceeds normal levels and can be caused by excessive eating patterns, such as fast food and junk food. The study aims to determine the effect of eating patterns on adolescents' overweight status. This quantitative study used an analytical observational method with a cross-sectional design. The sample consisted of 225 Vocational High School (SMK) Muhammadiyah 3 Purwokerto students, selected through cluster random sampling. The data used in this study included questionnaires on eating patterns and measurements of weight, height, mid-upper arm circumference, and waist circumference to assess overweight status. The eating pattern questionnaire comprised 20 items, of which 17 were valid. Validity results showed a minimum correlation coefficient (r) of 0.339 and a maximum of 0.550, with a critical value for n = 35 being 0.334. Reliability analysis using Cronbach's alpha yielded a value of 0.534. Data analysis was performed using the chi-square test. In the overweight group, eating patterns were categorized as high risk. In the non-overweight group, eating patterns were categorized as low risk. The chi-square test result showed a p-value of 0.0001 (p 0.05), indicating a significant effect of eating patterns on overweight status. Eating patterns significantly affect overweight status in adolescents at SMK Muhammadiyah 3 Purwokerto.